Experimental and numerical study of diffuser augmented wind turbine - Dawt - Maia, Lino André Bala (2019)
In this work was studied the effect of a shrouded structure around a small wind turbine. The objective was assessing the induced increment on their productivity, evaluating power coefficient. Laboratory measurements showed that improvements were obtained on electrical output, resulting in a maximum increase of 120 %. Measurements showed a power augmentation by a factor about 1.5-2.3, compared with the rotor without the shroud. Where a more pronounced augmentation is achieved at lower velocities. These increments attained, comparatively with previous studies, are shown in the same order of magnitude. Whereas an enhancement more pronounced relative to previous studies made for distinct shroud designs. Numerical simulations implemented in ANSYS FLUENT, modelled the rotor performance describing a non-similar trend on their respective power coefficients, comparatively with those obtained in experimentally. CFD calculations were performed at flow (Re=25343) with values of 6 and 14 m/s to the C-D device. CFD calculations performed an evaluation of the velocity experienced in the action rotor zone, which provided maximum increase of these air velocities of 81 % and 86 %, respectively.